INTERPERSONAL METAPHOR IN MATA NAJWA’S TALK SHOW - Elisa Perdana; Amrin Saragih (State University of Medan, 2013)
ABSTRACT This study investigate interpersonal metaphor in Mata Najwa’s talk show texts. Three are reasearch problems are raised, namely 1) What types of grammatical metaphors are used in Mata Najwa’s talk show. 2) How is interpersonal metaphor coded in Mata Najwa’s talk show. 3) In what contexts are the interpersonal metaphors coded as they are in Mata Najwa’s talk show. The analysis based on interpersonal metaphor as developed in Systematic Functional Linguistics (SFL). Specifically, dealt with interpersonal metaphor, in this study consist of two types, namely, metaphor of mood and metaphor of modaly. The total calculations are the metaphor of mood in Sang Penantang is about 94.85% and metaphor of modality is about 5.14%. The metaphor of mood in Sengatan Dahlan is about 95.34%and metaphor of modality is about 4.65%.In the investigating metaphor of mood is the dominant because the message of the sentences in political interaction used the patterns of mood which are seen as carrying the burden for making the different interpretation in the contextual occurences. Keyword: Interpersonal Metaphor, Talk show.